2019
DOI: 10.1128/aac.00420-19
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inactivation of Clinically Relevant Antimicrobial Drug Concentrations by BacT/Alert or Bactec Resin-Containing Media in Simulated Adult Blood Cultures

Abstract: We assessed the antimicrobial-inactivation capability of BacT/Alert (FA Plus and FN Plus) or Bactec (Plus Aerobic/F and Plus Anaerobic/F) media for 40 antibiotic-bacterium combinations in simulated adult blood cultures. Aside from high recovery rates (93.2% and 88.4%, respectively), we showed that at the lowest but clinically relevant antibiotic concentrations, both BacT/Alert and Bactec media recovered all the organisms tested with drugs except for Escherichia coli, which was tested in the presence of meropen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 19 publications
(13 reference statements)
2
17
4
Order By: Relevance
“…Interestingly, Menchinelli and colleagues recently reported P. aeruginosa recovery at all tested concentrations of meropenem, which were higher than the ones used here, whereas this study only had trough bottles alarm positive (19). This difference in observations may be attributed to the higher target used for the starting inoculums (50 to 100 CFU per 0.5 ml versus 7 to 30 CFU per 0.5 ml) (19). While the above conclusions are well supported for P. aeruginosa, the results against E. coli and K. pneumoniae were not as clear.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, Menchinelli and colleagues recently reported P. aeruginosa recovery at all tested concentrations of meropenem, which were higher than the ones used here, whereas this study only had trough bottles alarm positive (19). This difference in observations may be attributed to the higher target used for the starting inoculums (50 to 100 CFU per 0.5 ml versus 7 to 30 CFU per 0.5 ml) (19). While the above conclusions are well supported for P. aeruginosa, the results against E. coli and K. pneumoniae were not as clear.…”
Section: Discussioncontrasting
confidence: 79%
“…the conclusions of Grupper and colleagues (10) in that collection of blood cultures right before the scheduled dose, when antibiotic concentrations are predicted to be the lowest, should be a best practice for obtaining blood cultures for patients already receiving antibiotics. Interestingly, Menchinelli and colleagues recently reported P. aeruginosa recovery at all tested concentrations of meropenem, which were higher than the ones used here, whereas this study only had trough bottles alarm positive (19). This difference in observations may be attributed to the higher target used for the starting inoculums (50 to 100 CFU per 0.5 ml versus 7 to 30 CFU per 0.5 ml) (19).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…These data suggest that the greatest likelihood of recovery overall will be in the presence of trough concentrations. Our observations are largely similar to past studies, with a few notable exceptions (9,(11)(12)(13)23). In a recent study, Menchinelli and colleagues observed sterilization of all E. coli-inoculated anaerobic bottles exposed to meropenem (23), whereas we detected recovery at the midpoint and trough concentrations in the BacT/Alert bottles.…”
Section: Discussionsupporting
confidence: 91%
“…Until now, several blood culture simulation studies (involving blood culture bottles injected with whole blood, antimicrobial agents, and microorganisms) have compared the antimicrobial inactivation efficiency of BacT/ALERT FAN Plus media and BACTEC Plus media, including in both anaerobic and aerobic blood culture bottles. 6 , 7 However, since the BacT/ALERT FAN Plus media was only recently approved in the Chinese mainland, data on the performance of antimicrobial agent inactivation of BacT/ALERT FAN Plus media from China mainland is not yet available.…”
Section: Introductionmentioning
confidence: 99%